The Effects Of Job Resources And Job Demands On Teachers' Organizational Citizenship Behavior : The Role Of Burnout As A Mediator - Meh, Salmi Che (2012)
Organizational Citizenship Behavior (OCB) has generated a considerable amount of scholarly attention. It is now firmly believed that the effective functioning of an organization depends largely on employees’ efforts that extend beyond formal role requirements. Due to the paucity of research in non-commercial setting, specifically service occupation, this study attempts to uncover how job resources (supervisor support, peer support, autonomy, and participation in decision making) and job demands (role ambiguity, role conflict, role overload, and students’ misbehavior) influence teachers’ organizational citizenship behavior. This study also investigates whether the role of burnout would mediate the relationship between job resources, job demands and organizational citizenship behavior. Data were obtained through mailed survey from 509 teachers in 50 regular government secondary schools in Peninsular Malaysia. Findings of this study revealed two dimensions of organizational citizenship which are organizational citizenship behavior targeted at the organization/OCB-O (school), and organizational citizenship behavior targeted at the individual/OCB-I (students and peers). The findings provided some empirical support for the framework. The results provided evidence that job resources and job demands played important roles in influencing teachers’ organizational citizenship behavior. The findings also demonstrated some evidence to support the mediating effect of burnout on the relationship between job resources, job demands and organizational citizenship behavior. Theoretical and practical implications of the study as well as suggestions for future studies were discussed.